The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41419-018-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-455-3p inhibits the degenerate process of chondrogenic differentiation through modification of DNA methylation

Abstract: The aim of this work was to determine whether miR-455-3p regulates DNA methylation during chondrogenic differentiation of hMSCs. The expression of miR-455-3p and de novo methyltransferase DNMT3A was assessed in micromass culture of hBMSCs, which induced chondrogenic differentiation in vitro, and in E16.5 mice in vivo. A luciferase reporter assay was used to confirm whether miR-455-3p directly targets DNMT3A by interaction with the 3′-UTR. Using an Illumina Infinium Methylation EPIC microarray, genome-wide DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Recent advances in epigenetic research have shed light on the importance of microRNA (miRNA) in the regulation of gene expression at multiple levels related to the pathogenesis of OA [18]. In a previous study, we reported significant up-regulation of the miRNAs, miR-381-3p, miR-455-3p, miR-193b-3p, and miR-92a-3p during differentiation of human mesenchymal stem cells into chondrocytes, and provided evidence that these four miRNAs may regulate early chondrogenesis and cartilage degeneration [19][20][21][22][23][24]. However, the expression profile of the miRNAs in the menisci with tears is unknown.…”
Section: Introductionmentioning
confidence: 93%
“…Recent advances in epigenetic research have shed light on the importance of microRNA (miRNA) in the regulation of gene expression at multiple levels related to the pathogenesis of OA [18]. In a previous study, we reported significant up-regulation of the miRNAs, miR-381-3p, miR-455-3p, miR-193b-3p, and miR-92a-3p during differentiation of human mesenchymal stem cells into chondrocytes, and provided evidence that these four miRNAs may regulate early chondrogenesis and cartilage degeneration [19][20][21][22][23][24]. However, the expression profile of the miRNAs in the menisci with tears is unknown.…”
Section: Introductionmentioning
confidence: 93%
“…MiRNAs (∼22-nt) are robust regulators of post-transcriptional gene expression with a high affinity for the 3′ untranslated region, ultimately carrying out their function through recruitment of protein complexes that block ribosomal translation and contribute to degradation of the poly-adenylated tail (Bartel, 2004). Previously, we reported a 2.973-fold upregulation of miR-455-3p upon differentiation of human adipose-derived stem cells into chondrocytes (Zhang et al, 2012) and provided evidence that miR-455-3p is an important regulator of chondrogenesis and cartilage degeneration via the inhibition of RUNX2/HDAC2/HDAC8/DNMT3A (Zhang et al, 2015; Chen et al, 2016; Sun H. et al, 2018). Although studies of miRNAs have dominated the field of RNA biology in recent years, accumulating evidence shows that lncRNAs (>200-nt) are central regulators of biological processes, including those involved in the pathology of OA (Liu et al, 2014; Xing et al, 2014; Pearson et al, 2016); they regulate gene expression at both the transcriptional and post-transcriptional levels (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…A new regulatory mechanism has been identified that ncRNAs, such as lncRNAs and miR-NAs, can be potential triggers in the decision of cell fates by methylated modification. For example, lncRNA Plnc1 was reported to mediate the differentiation of bone marrow stromal cells (BMSCs) into adipocytes by DNA methylation [32], and miRNA-455-3p changed the methylation status of chondrogenic-specific genes during the differentiation of human bone marrow mesenchymal stem cells (hBMSCs) towards chondrocytes [33], which would be discussed in more detail in later sections.…”
Section: Cells Differentiationmentioning
confidence: 99%
“…It was reported that miR-455-3p directly targeted the 3′-UTR of DNMT3A and regulated the process of chondrogenic differentiation in hBMSCs by altering the methylation levels of genes associated with cartilage development. Most of these genes, including FOXO3A, SMAD3, COL11A1, and SOX6, were hypomethylated and involved in the P13K-Akt signaling pathway [33], revealing the hypomethylated signaling pathway was a crucial regulator of chondrogenic differentiation.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%